Enhancing College Student Leadership Practices Through Organization Development Interventions: A Case Study of Zhejiang Yuexiu University of Foreign Languages (Zyufl), China - Ding, Xiaoyang; Ye, Yan (Scholar: Human Sciences, 2021)
This research mainly investigated the impact of ODI on the leadership practice of college students, to determine the significant difference in university student leadership before and after ODI. The researcher firstly surveyed on 339 students in ZYUFL Jinghu Campus to study the current university students’ leadership practice, it was found that the level of leadership of college students was not high. Meanwhile, significant differences of the students’ leadership practices according to their experiences of knowledge learning, practical training, and team building were determined. Based on these findings, the researcher had designed relevant leadership activities, and conducted a four-month intervention for improving the selected college students’ leadership practices. Then, the researcher further tested and compared the students’ leadership practices in the control group and the experimental group, before and after the intervention. In this process, a paired samples t-test was applied and significant differences with the students in the experimental group before and after the intervention were determined, which proved that the intervention was effective, and the college students’ leadership practice could be effective through intervention. Discussion on the findings and recommendations were also provided in this study.